Best practice approach to stage-discharge rating curve: case study of selected rivers in Selangor / Azlinda Saadon ... [et al.] - Saadon, Azlinda; Abdul Manaf, Nur Anim; Tholibon, Duratul Ain; Ahmad Kamal, Norashikin; Yassin, Ahmad Ihsan (2023)
A stage-discharge rating curve represents the relationship between the water level at a given point in a stream and a corresponding volumetric rate of flow. It is widely used for the analysis of flow regimes, designing hydraulic structures, flood forecasting, flow-sediment interaction and prediction, and river channel analysis. The reliability and stability of the stage-discharge rating curve are based on numerous numbers of discharges and stage data from the lowest to the highest bank full stage observed over a long period of time. Stage-discharge rating curves contribute to reliable discharge prediction for future flood forecasting. This study focuses on the best-practice approach to stage-discharge rating curve development for selected rivers in Selangor. The stage-discharge rating curve derived was evaluated in terms of the statistical parameter, which denotes the degree of determination or r-squared value. The polynomial function yields better accuracy at 68.6% than the exponential function at 60.3%. Model validation was performed using the discrepancy ratio and confirmed that the stage-discharge rating curve developed using both mathematical functions give good predictions with more than 80% accuracy for the specified flow range and stage levels.